Financialisation and the sub-prime crisis: a stock-flow consistent model - Eugenio Caverzasi; Antoine Godin (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
Our opinion is that the so-called sub-prime mortgage crisis has been a structural crisis of the US's financial capitalism. In analysing the complex combination of factors that led to those events, we try not to focus on the most contingent aspects but to clarify the underlying structure that made the crisis endogenously emerge from the US's economic system. To reach this goal, we base our analysis on existing economic theories. In particular, the combination of the Financial Instability Hypothesis by Hyman Minsky, the theory of Capital Market Inflation by Jan Toporowski, and the post-Keynesian literature on financialisation represent the foundation of our analysis. The results of our analysis will then be reproduced through a simulated stock-flow consistent model to test their logical coherence.
Keywords: E12; E37; G21; 330; Minsky; stock-flow consistent; financialisation; banks